Probiotics for the improvement of metabolic profiles in patients with metabolic-associated fatty liver disease: A systematic review and meta-analysis of randomized controlled trials - Wang, Qiuhong; Wang, Ze; Pang, Boxian; Zheng, Huijuan; Cao, Zhengmin; Feng, Chunpeng; Ma, Wenxin; Wei, Junping (Frontiers in Endocrinology, 2022)
Objective This meta-analysis of randomized controlled trials (RCTs) was conducted to assess the efficacy of probiotics in the treatment of metabolic-associated fatty liver disease (MAFLD) mainly in terms of liver function, glucose and lipid metabolism, and inflammation. Methods RCTs were searched on PubMed, Web of Science, Embase, and the Cochrane Library until June 2022. A meta-analysis was performed on the therapeutic efficacy of probiotics on liver function, glucose and lipid metabolism, and inflammatory biomarkers by using RevMan 5.4 software. Results A total of 772 patients from 15 studies were included in the analysis. The methodological quality varied across studies. We found that adding probiotic therapies could reduce the levels of alanine aminotransferase [mean difference (MD): −11.76 (−16.06, −7.46), p < 0.00001], aspartate aminotransferase (MD: −9.08 (−13.60, −4.56), p < 0.0001], γ-glutamyltransferase [MD: −5.67 (−6.80, −4.54), p < 0.00001] and homeostasis model assessment–insulin resistance [MD: −0.62 (−1.08, −0.15), p = 0.01], in patients with MAFLD compared with those in control individuals. However, there was no statistically significant improvement in the levels of total cholesterol, triglycerides, low-density lipoprotein cholesterol, C-reactive protein and tumor necrosis factor α among patients with MAFLD. Subgroup analyses showed that other key factors, such as age, participants’ baseline body mass index, and the duration of intervention, may influence probiotic therapy outcomes. Conclusion There is promising evidence that probiotic supplementation can reduce liver enzyme levels and regulate glycometabolism in patients with MAFLD. Further rigorous and long-term trials exploring these novel therapeutic perspectives are warranted to confirm these results.